Livestock production in central Mali: Factors influencing growth and liveweight in agro-pastoral cattle - Wilson, R.T. (Springer, 1987)
Reports the results of studies on growth and live weight changes in a sedentary agro-pastoral system (Mali). Estimates weight & growth by age, sex, season & year, parity and farming system.